2010
DOI: 10.1007/s11605-009-0910-y
|View full text |Cite
|
Sign up to set email alerts
|

Primary Omental Mesothelioma: A Rare but Important Differential Diagnosis in Previous Asbestos Exposure

Abstract: Primary omental mesothelioma is a malignant tumour of the mesothelial cells of the omentum, related to asbestos exposure. It is an extremely rare condition that presents both diagnostic and therapeutic challenges. We present a review of the related literature and report on a fatal case of primary omental mesothelioma in a 70 year old man, presenting with a painful abdominal mass. Radiological imaging was not diagnostic but useful in excluding other pathologies. Diagnosis relied on specific immunohistochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Epidemiological trials have demonstrated an association between the occurrence of mesothelioma and environmental factors and carcinogens. The association between mesothelioma and asbestos was first demonstrated in 1960 by Wagner et al In most of the cases presented in literature, there is a history of apparent asbestos exposure and of living close to regions where asbestos is intensively used [4,8]. Asbestos exposure was present in our patient and a previous case [4] but not in another case [3].…”
Section: Akkaya Et Al 72 Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…Epidemiological trials have demonstrated an association between the occurrence of mesothelioma and environmental factors and carcinogens. The association between mesothelioma and asbestos was first demonstrated in 1960 by Wagner et al In most of the cases presented in literature, there is a history of apparent asbestos exposure and of living close to regions where asbestos is intensively used [4,8]. Asbestos exposure was present in our patient and a previous case [4] but not in another case [3].…”
Section: Akkaya Et Al 72 Discussionmentioning
confidence: 50%
“…Peritoneal involvement usually manifests as abdominal distention, anorexia, weight loss, and symptomatic malignant ascites. However, ascites was not reported in a previous case with omental mesothelioma [4]. Ascites was present in three out of four cases with primary omental mesothelioma.…”
Section: Akkaya Et Al 72 Discussionmentioning
confidence: 66%
See 3 more Smart Citations